Service Quality of Satu Data in Banten Province, Indonesia - Mahmud, Toni Anwar; Myrna, Rita; Rusli, Budiman; Sumaryana, Asep (KnE Social Sciences, 2022)
Public services carried out by the government aim to meet the needs and interests of the community. The Banten Provincial Government has various regulations regarding electronic-based public services. However, there are still many challenges. The purpose of this study was to determine the quality of electronic public services carried out by the Banten Provincial Government. Descriptive methods were used and data were collected through a literature review. The results indicated that the quality of services can be evaluated across four dimensions, namely efficiency, fulfillment, system availability and privacy, but that none of these have been fully met. This can be seen given the variety of domains provided; there are still menus and submenus on the website that do not have content and are not updated; the technology used is still prioritizing using the website and still uses third-party services; and there is a lack of human resources, infrastructure facilities and personnel who have skills in security systems to maintain the confidentiality of public-private data. Keywords: satu data, public service, electronic-based government system